Zero product property Part II

classic Classic list List threaded Threaded
2 messages Options
Kenneth Kenneth
Reply | Threaded
Open this post in threaded view
|

Zero product property Part II

Just a simple question I have,

1. (X-1)(2x+9)=(X-3)(X+3)


AlgebraHouse AlgebraHouse
Reply | Threaded
Open this post in threaded view
|

Re: Zero product property Part II

 (X-1)(2x+9) = (X-3)(X+3)
2x² + 7x - 9 = x² - 9 {multiplied binomials using foil method}
x² + 7x = 0 {subtracted x² and added 9 to both sides}
x(x + 7) = 0 {factored x out}
x = 0 or x + 7 = 0 {set each factor equal to 0}
x = 0 or x = -7 {solved each equation for x}

- Algebra House